The relationship of science process skills and students' critical thinking skills in momentum and impulse materials - Astalini, Astalini; Darmaji, Darmaji; Kurniawan, Dwi Agus; Triani, Elza; Oktavia, Sri Wina (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2024)
This study aimed to see the description and relationship between students' science process skills and critical thinking skills of 10th graders at SMAN 10 Jambi City in the Physics subject of Momentum and Impulse. This type of research uses the Mix Method research method. Researchers took random samples in 2 classes, namely 10 IPA 1 and 10 IPA 3 at SMAN 10 Jambi City, with a total of 25 students in each class, so the number of samples used was 50. Data analysis began with a descriptive test and then tested the hypothesis using correlation analysis techniques and analysis of interview results. The results showed a significant relationship between the students' science process skills and the critical thinking skills of the 10th graders of SMAN 10 Jambi City in the Physics subject of Momentum and Impulse. Implications This research is expected to help students and teachers identify descriptions and relationships between students' science process skills and 10th-grade students' critical thinking skills, especially in Momentum and Impulse materials.